2018
DOI: 10.1111/gcb.14049
|View full text |Cite
|
Sign up to set email alerts
|

Is salinity an obstacle for biological invasions?

Abstract: Our study revealed that all tested populations tolerate wide ranges of salinity, however, different patterns arose among species from different regions. Ponto-Caspian taxa showed lower mortality in fresh water, while Northern European taxa showed lower mortality in fully marine conditions. Genetic analyses showed evolutionary divergence among species from different regions. Due to the geological history of the two regions, as well as high tolerance of Ponto-Caspian species to fresh water, whereas Northern Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
81
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(105 citation statements)
references
References 74 publications
11
81
8
Order By: Relevance
“…In addition, several previous studies reported that G. tigrinus can tolerate temperatures up to 30°C in brackish environments, and it thrives in heavily polluted waters (Pinkster et al., ; Ruoff, ; Savage, ; Wijnhoven, Van Riel, & van der Velde, ), while Paiva et al. () determined different salinity tolerance among populations of that species and seven others. In the population used in our experiments, dark spots were regularly observed on animals.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In addition, several previous studies reported that G. tigrinus can tolerate temperatures up to 30°C in brackish environments, and it thrives in heavily polluted waters (Pinkster et al., ; Ruoff, ; Savage, ; Wijnhoven, Van Riel, & van der Velde, ), while Paiva et al. () determined different salinity tolerance among populations of that species and seven others. In the population used in our experiments, dark spots were regularly observed on animals.…”
Section: Discussionmentioning
confidence: 96%
“…However, Paiva et al. () reported different salinity tolerance among populations for the same eight gammarid species indicating that neutral genetic markers, such as mtDNA‐COI, are not able to detect population adaptation to different salinities and genome‐wide screening, particularly of coding regions, is necessary to determine adaptation to local environmental conditions. While, we are not aware of any study connecting temperature tolerance and populations for any species, we believe that the same would apply for adaptation to different temperature tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations